1968
DOI: 10.1001/archpedi.1968.02100010496016
|View full text |Cite
|
Sign up to set email alerts
|

Granulosa-Theca-Cell Tumor of the Ovary in Children

Abstract: WITHIN RECENT years granulosa\x=req-\ theca-cell tumors have attracted much interest, primarily because of their hormonal function. These tumors are the principal feminizing neoplasms of the ovary; and it has been emphasized that when they occur in prepubertal females, they almost always cause sexual precocity. Because of this known and rather constant relationship, the diagnosis of granulosa-theca-cell tumor usually is entertained in the differential diagnosis of isosexual precocity in females. Although it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
1997
1997

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The occurrence of the tumour in children and its relation to precocious puberty have been reviewed by Zangeneh and Kelley (1968) with no suggestion that the neoplasm behaves in any significantly different way in childhood. Two series of cases that they cite had a combined mortality of 12.5%.…”
Section: Granulosa-theca Cell Tumourmentioning
confidence: 99%
“…The occurrence of the tumour in children and its relation to precocious puberty have been reviewed by Zangeneh and Kelley (1968) with no suggestion that the neoplasm behaves in any significantly different way in childhood. Two series of cases that they cite had a combined mortality of 12.5%.…”
Section: Granulosa-theca Cell Tumourmentioning
confidence: 99%
“…This is usually impossible in advanced tumors which have spread beyond the ovary but might be achieved in early incapsulated tumors. Survival of girls with ovarian carcinoma is universally conceded to be low, regardless of the stage, histological type, age, or therapy, the only exception being the dysgerrninoma and the thecagranulosa cell tumor types, where the outlook is good (2, 3,15). It has been observed that even in patients with early tumors (Stage I and 11) other than the above, it is difficult to control the disease when primary treatment is unsuccessful, indicating that conservative surgery fails to identify and remove all tumor foci (3).…”
Section: Introductionmentioning
confidence: 99%